Genome-wide association study of short-acting β2-agonists. A novel genome-wide significant locus on chromosome 2 near ASB3 - Israel, Elliot; Lasky-Su, Jessica; Markezich, Amy; Damask, Amy; Szefler, Stanley J; Schuemann, Brooke; Klanderman, Barbara; Sylvia, Jody; Kazani, Shamsah; Wu, Rongling; Martinez, Fernando; Boushey, Homer A; et al. (American journal of respiratory and critical care medicine, 2015)
β2-Agonists are the most common form of treatment of asthma, but there is significant variability in response to these medications. A significant proportion of this responsiveness may be heritable. To investigate whether a genome-wide association study (GWAS) could identify novel pharmacogenetic loci in asthma. We performed a GWAS of acute bronchodilator response (BDR) to inhaled β2-agonists. A total of 444,088 single-nucleotide polymorphisms (SNPs) were examined in 724 individuals from the SNP Health Association Resource (SHARe) Asthma Resource Project (SHARP). The top 50 SNPs were carried forward to replication in a population of 444 individuals. The combined P value for four SNPs reached statistical genome-wide significance aftercorrecting for multiple comparisons. Combined P values for rs350729, rs1840321, rs1384918, and rs1319797 were 2.21 × 10(-10), 5.75 × 10(-8), 9.3 × 10(-8), and 3.95 × 10(-8), respectively. The significant variants all map to a novel genetic region on chromosome 2 near the ASB3 gene, a region associated with smooth muscle proliferation. As compared with the wild type, the presence of the minor alleles reduced the degree of BDR by 20% in the original population and by a similar percentage in the confirmatory population. These GWAS findings for BDR in subjects with asthma suggest that a gene associated with smooth muscle proliferation may influence a proportion of the smooth muscle relaxation that occurs in asthma.